2020
DOI: 10.1002/ejic.202000771
|View full text |Cite
|
Sign up to set email alerts
|

PdII(P‐P) Derivatives of o‐Quinone Annulated with Dithiete Cycle: Electrochemical Properties and Coordination Regioisomerism

Abstract: Regioselectivity in interaction of bifunctional o‐quinone annulated with dithiete cycle with tris(dibenzylideneacetone)dipalladium (Pd2dba3) in presence of bidentate phosphines was studied. Excluding the case of 1,2‐bis(diphenylphosphino)ethane (dppe) species, the formation of corresponding dithiolates with high yields was observed. Coordination of palladium to the dithiolene site of bifunctional ligand causes a distortion of the dioxolene site as well as significant decrease of its electron‐acceptor ability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The asymmetric unit is composed of eight molecules [Dy(hfac)3(H2O)(L 2 )] (Figure 2a) and its ORTEP view is shown in Figures S3 and S4. The bischelating dioxolene site in a quinone form is coordinated to the [Dy(hfac)3(H2O)] unit, in agreement with the oxophilic character of the lanthanide ion, in contrast with what was observed for the bischelating dithiolene coordination site, which is coordinated to the soft Pd II [34]. The quinone form of L 2 was confirmed by the C=O bond lengths, ranging from 1.064 Å to 1.417 Å (average distance of 1.230 Å).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The asymmetric unit is composed of eight molecules [Dy(hfac)3(H2O)(L 2 )] (Figure 2a) and its ORTEP view is shown in Figures S3 and S4. The bischelating dioxolene site in a quinone form is coordinated to the [Dy(hfac)3(H2O)] unit, in agreement with the oxophilic character of the lanthanide ion, in contrast with what was observed for the bischelating dithiolene coordination site, which is coordinated to the soft Pd II [34]. The quinone form of L 2 was confirmed by the C=O bond lengths, ranging from 1.064 Å to 1.417 Å (average distance of 1.230 Å).…”
Section: Resultssupporting
confidence: 68%
“…Some of us previously demonstrated that single-and two-electrons reduction led to the respective formation of semiquinonate species and catecholate or dithiolate species depending on the nature of the metallo-fragments. Moreover, a regioselectivity of the coordination reaction was observed depending on the hard or soft acidity of the metal ion [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] The geometry of the dithiete four-membered ring (SÀ S 2.103(2) Å, CÀ S 1.784(3)-1.786(3) Å) in 5 is similar to parent o-quinone 1, as in the previously reported Pd catecholate complex. [7][8][9] Since, to the best of our knowledge, complex 7 (Scheme 4) reported by Kaizer et al [29] is the only structurally characterized four-coordinated copper catecholate adduct with TMEDA, we additionally synthesized and examined one more Cu(II) complex with 3,6-di-tert-butyl-o-benzoquinone 6. (Figure 1 65 Cu, S = 3/2).…”
Section: Resultsmentioning
confidence: 99%
“…[5] Recently we reported the coordination properties of the oquinone annulated with dithiete cycle 1. [6][7][8][9] Functionalization of the o-quinone molecule with an additional chelating coordination site converted it into bridging ligand possessing a rigid and almost planar structure. Such a topology is promising in terms of construction of coordination polymers.…”
Section: Introductionmentioning
confidence: 99%
“…15 This methodology has recently been exploited by Fekl and Kuropatov who examined oxidative addition of dithietes to Pd(0). 16,17 In this context, we have explored the related benzo-fused1,2,5,6-tetrathiocins which can be considered as dimers of the dithiete moiety and exhibit similar reactivity to zero-valent group 10 metal complexes. 18−23 The current study describes a simple two-step synthesis of benzo-crown functionalized derivatives 3 and 4 and explores their reactivity with selected alkali metal ions (Na + , K + , Rb + , and Cs + ) and 3d metal ions (Co 2+ and Cu 2+ ), focusing on the stoichiometry of coordination and the nature of the products formed through oxidation.…”
Section: ■ Introductionmentioning
confidence: 99%